Flight Cancellations: Infringement of the Carriage Agreement Between Airlines and Passengers - Sitompul, Rifqi Ananda Gelora (Universitas Islam Indonesia, 2024)
Flight cancellations lead to passenger inconvenience and financial loss, as pre-purchased plane tickets are rendered null and void. The primary objective of this research is to examine whether flight cancellations by airlines, impacting passengers as consumers, constitute a breach of contract or not. This research also identified the legal responsibilities of airlines as business entities in such scenarios. Several research questions were proposed. The first issue is whether flight cancellations by airlines for passengers as consumers represent a breach of contract?; Second, we examined the legal responsibilities of airlines towards passengers as consumers when flights are canceled. Finally, we approached the legal responsibility of airlines for cancelled flights from a prophetic law perspective. In this normative research, a statutory approach was used to analyze the legal framework on the issue. This research regarded secondary data collected through library research, including primary, secondary, and tertiary legal materials. This research concludes that airline flight cancellations constitute a breach of contract from the perspective of passengers as consumers under Indonesian law. Besides that, two primary forms of legal responsibilities for airlines in cases of flight cancellations were identified. Airlines can either rebook affected passengers on the next available flight or refund the full ticket price previously paid by the passenger in cash and non-cash compensation. Moreover, those legal responsibilities imposed on the airlines are known in Islamic law with the ‘daman’ concept and in line with prophetic law pillars.